Identifying and Ranking Core Components of Organizational Wellness Systems Improving Productivity - Karimov, Dilshod; Rahman, Farid Hakim; Christou, Eleni (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to identify and rank the core components of organizational wellness systems that most effectively enhance employee productivity. This research followed a mixed-methods sequential design. In the first phase, a qualitative literature review was conducted until theoretical saturation was achieved, and all extracted data were coded and analyzed using NVivo 14 to identify wellness components. In the second phase, these components were operationalized into a structured questionnaire and distributed to 240 employees from various organizational sectors in Malaysia. Data from the quantitative phase were analyzed using SPSS-26 through descriptive statistics, reliability testing, and ranking procedures to determine the relative importance of each wellness component. Quantitative rankings revealed eight major components with varying levels of influence on productivity. Leadership and Organizational Culture received the highest mean importance score (M = 4.80), followed by Psychological and Emotional Wellness (M = 4.70) and Organizational Policies and Support Systems (M = 4.60). Mid-range rankings included Career Growth and Professional Development (M = 4.50) and Work Environment and Organizational Design (M = 4.40). Lower-ranked but still important dimensions included Employee Physical Wellness (M = 4.30), Social and Interpersonal Wellness (M = 4.20), and Organizational Communication and Engagement (M = 4.10). All components demonstrated strong relevance to productivity enhancement. The study confirms that organizational wellness is a multidimensional construct in which leadership quality, psychological support, and institutional policies form the most significant pillars of productivity. The findings emphasize the need for integrated wellness systems that balance mental, physical, structural, social, and developmental components. Organizations seeking to improve productivity should prioritize leadership development, psychological wellness programs, and comprehensive support policies while maintaining systemic attention to all dimensions of wellness.